HE INFLUENCE OF INFLUENCER MARKETING AND BRAND AWARENESS ON PURCHASE DECISIONS FOR SKINTIFIC PRODUCTS ON TIKTOK SHOP IN BOGOR REGENCY - Icca Apriliyanti; B. Retno Pratiwi Sakti (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of Influencer Marketing and Brand Awareness on Purchasing Decisions of Skintific products on TikTok Shop in Bogor Regency. The development of social media, especially TikTok, has driven changes in consumer behavior in seeking information and purchasing products. Therefore, digital-based marketing strategies such as the use of influencers and increasing brand awareness have become very important. The method used in this study is a quantitative approach with a descriptive-verificative research type. The population in this study consisted of TikTok Shop users in Bogor Regency, with a sample of 102 respondents. Data were collected through questionnaires distributed to respondents who had seen or purchased Skintific products. The data analysis techniques used included validity testing, reliability testing, linear regression analysis, and hypothesis testing to examine the influence among variables. This study is expected to contribute to companies in designing effective digital marketing strategies, particularly in utilizing influencer marketing and increasing brand awareness to encourage sustainable consumer purchasing decisions.